Leucodystrophies at children - Wiktoria Sielwanowska; Bartłomiej Syzdoł; Anna Rzewuska; Monika Żybowska; Magdalena Chrościńska-Krawczyk (Kazimierz Wielki University, 2023)
Introduction   Leukodystrophies involve a diverse group of rare hereditary disorders mostly affecting the white matter of the central nervous system, which straddleses nerves and glial cells. Unfortunately, these conditions are often undervalued by doctors from various specialties. The aim of the article was to present the most common leukodystrophies occurring in children  Material and methods  A review of the most common leukodystrophies based on the available literature. We conducted a systematic literature review. We searched the PubMed and Google Scholar databases from 1997 to 2023.  Conclusions  Leukodystrophies are rare genetic diseases that often present with non-specific symptoms, which can pose diagnostic challenges. Ocular abnormalities and psychomotor delay in the early stages of life should raise suspicion. A combination of symptoms may suggest a pyramidal-extrapyramidal form of cerebral palsy. Therefore, it is crucial to include a head MRI examination in the diagnostic workup and carefully evaluate the findings, as subtle imaging changes can indicate the presence of leukodystrophies. Currently, no causal treatment for leukodystrophies has been developed. Hence, further research is needed to enable the introduction of gene therapies.